A Case Control Study to Elucidate the Effects of Maternal Anthropometric Characteristics and Other Factors on Birth Weight of Newborn - Suryavanshi, Jaya V; Shingade, Poonam P (National Journal of Community Medicine, 2018)
Background: Birth weight reflects mother’s health and nutritional status during pregnancy. This study was conducted to measure the effect of various maternal factors on birth weight; and also to study the strength of association between risk factors and low birth weight. Methods: A case-control study was conducted among neonates delivered in tertiary care Hospital from June 2013 to July 2014 among mothers who delivered in the hospital and their singleton newborns. Birth weight was measured for all newborns and these mothers undergone anthropometric measurements and were asked relevant questions. Results: The proportion of low birth weight was 27.73%. Maternal age of more than 30 years (odds ratio 1.98; χ2=3.86, P=0.04), gestational age at the time of birth (OR 4.37; χ2=44.21, P=0.000) occupation of mother (OR 1.69, χ2=4.54, P=0.03) maternal height <145 cm (OR 2.74, χ2=17.97, P= 0.000), maternal weight <45 kg (OR 1.90, X2 =8.19, P= 0.004) and complications during pregnancy (OR 1.78 χ2=6.55, P =0.01) have a significant association with LBW infant. Conclusion: LBW rate was higher when Maternal age more than 30, early gestational age at the time of birth, occupation of mother, maternal height <145 cm, maternal weight < 45 kg and complications during pregnancy.